Profit Leveling Actions in Banking in terms of Profitability, Company Size and Capital Structure - Amin, Asbi; Hala, Yusriadi; Rinaldy, Syiar (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2023)
This study aims to examine the effect of profitability, company size and capital structure on profit leveling practices in the banking sector listed on the Indonesia Stock Exchange for the 2020-2022 period. The type of research used is associative quantitative research. The population in this study is banking companies listed on the Indonesia Stock Exchange during 2020-2022, which is 47 companies. The sampling technique in this study is using purposive sampling techniques, so that the number of samples in this study is 84 sample data on financial statements of banking companies for the 2020-2022 research period. The data analysis method uses Logistic Regression analysis (logistic regression). The results of the study found that profitability has a positive and significant effect on profit smoothing in banking companies listed on the Indonesia Stock Exchange, Company size has no influence on profit smoothing in banking companies listed on the Indonesia Stock Exchange, Capital structure does not have a significant effect on profit smoothing in banking companies listed on the Indonesia Stock Exchange